Assessment of heavy metal pollution in abandoned Giap Lai pyrite mine (Phu Tho Province) - Xuan*, Pham Tich; Lien, Nguyen Thi; Dang, Pham Thanh; Tra, Doan Thi Thu; Pho, Nguyen Van; Qua, Nguyen Xuan; Nga, Hoang Thi Tuyet (Vietnam Journal of Earth Sciences, 2017)
Giap Lai pyrite mine had been exploited in the period 1975 - 1999, and abandoned after the mine became closed. This work is conducted with the aim to evaluate the impacts of the abandoned mine to the environment. 23 surface water, 15 ground water and 20 soil samples from the mining area were collected for experiments. Acid production potential and metal leaching of waste materials from tailings were tested. Results show that acid rock drainage (ARD) in the old mining area still occurs, with sulfide-rich tailings and waste rocks being sources of ARD, causing elevated metal concentrations in downstream water bodies. Surface water shows significant pollution of Fe, Mn, Ni and partially As. In the rainy season, the percentage of surface water samples having low pH values as well as metal contents in samples is higher than in the dry season. Metal concentrations in ground water are generally low, but many samples have low pH values, indicating the influence of the ARD. The geo-accumulation index reveals that soil from mining area is moderately contaminated with Ni, Cu, Hg and partially As. Most of the polluted samples are located near old mining pits, waste dumps and tailing ponds. The study also shows that negative effect of Giap Lai pyrite mine on the surrounding water and soil has been ongoing. However, no post-closure remediation measures have been applied at the mine, so there must be appropriate solutions for the acid mine drainage treatment before its being discharged to the environment. Given the facts revealed by this study, it is recommended that the Environmental Protection Law should be fully implemented at mining sites not only during the exploitation but also after their closures. References AMIRA, 2002. ARD Test Handbook. Project P387A Prediction & Kinetic Control of Acid Mine Drainage. AMIRA international May 2002, 42p. Çevik, F., Göksu, M. Z. L., Derici, O. B., Fındık, Ö., 2009. An assessment of metal pollution in surface sediments of Seyhan dam by using enrichment factor, geoaccumulation index and statistical analyses. Environmental Monitoring and Assessment 152, 309-317. EPA, 2000. Abandoned mine site characterization and cleanup hand book, 129p, (https://yosemite.epa.gov/r10/amscch.pdf). Ghrefat, H.A., Abu-Rukah, Y., Rosen, M.A., 2011. Application of geoaccumulation index and enrichment factor for assessing metal contamination in the sediments of Kafrain Dam, Jordan. Environmental Monitoring and Assessment 178, 95-109. IAEA, 2000. Reference Sheet, reference material. Trace elements in soil. (https://nucleus.iaea.org/rpst/Documents/rs_iaea-soil-7.pdf). INAP, 2009. Global Acid Rock Drainage Guide. International Network for Acid Prevention. (http://www.gardguide.com/index.php/Main_Page). Loska, K., Wiechula, D., Korus, I. 2004. Metal contamination of farming soils affected by industry. Environment International, 30(2), 159-165. MCMPR/MCA, 2010. Strategic Framework for Managing Abandoned Mines in the Minerals Industry, http://www.industry.gov.au/resource/Mining/Documents/StrategicFrameworkforManagingAbandonedMines.pdf. Mhlongo, S.E. and Amponsah-Dacosta, F., 2015. A review of problems and solutions of abandoned mines in South Africa, International Journal of Mining, Reclamation and Environment, DOI: 10.1080/17480930.2015.1044046. Müller, G., 1969. Index of geoaccumulation in sediments of the Rhine River. Geojournal 2, 108-118. Newton, G., et al, 2000. California’s Abandoned Mines. A Report on the Magnitude and Scope of the Issue in the State, Vol.1, 60p. Http://www.conservation.ca.gov/omr/abandoned_mine_lands/AML_Report/Documents/volume1textonly.pdf Nordstrom, D.K., Alpers, C.N., 1999. Geochemistry of acid mine waste. In “Review in Economic Geology, the environmental geochemistry of ore deposits”/Eds. G.S.Plumlee, M.J. Logsdon. Part A: Processes, techniques, and health issues Vol.6A, 133-160. Nowrouzi, M. and Pourkhabbaz, A., 2014. Application of geoaccumulation index and enrichment factor for assessing metal contamination in the sediments of Hara Biosphere Reserve, Iran. Chemical Speciation and Bioavailability, 26(2),99-105. Pham Tich Xuan, Nguyen Van Pho, Hoang Tuyet Nga, Doan Thi Thu Tra, Cai Van Truong, Nguyen Van Thu, Vu Manh Long, 2010. Heavy metal pollution in some metal mines in the Northern Vietnam. Procceding of Conference in commemoration of the 35th day of Establish of VAST. Environment and Energy, Hanoi, 236-244 (in Vietnamese with English abstract). Sobek, A.A., Schuller, W.A., Freeman, J.R. and Smith, R.M., 1978. Field and laboratory methods applicable to overburden and minesoils. Report EPA 600/2-78-054, US Environmental Protection Agency, 204p. Tarras-Wahlberg N.H, Lan T. Nguyen, 2008. Environmental regulatory failure and metal contamination at the Giap Lai pyrite mine, Northern Vietnam. Journal of Environmental Management, 86(4), 712-720. Tran Xuan Toan, 1963. Some characteristics of pyrite mineralization in the Giap Lai deposit, Phu Thọ. Geology 10, 18-24, Hanoi (in Vietnamese). Wei, Z., Wang, D., Zhou, H., Qi, Z., 2011. Assessment of Soil Heavy Metal Pollution with Principal Component Analysis and Geoaccumulation Index. Procedia Environmental Sciences, 10, 1946 -1952. Zawadzki, J and P. Fabijan´czyk, P., 2013. Geostatistical evaluation of lead and zinc concentration in soils of an old mining area with complex land management. Int. J. Environ. Sci. Technol. 10, 729-742. Ziemkiewicz, P., J. Renton and T. Rymer, 1991. Prediction and Control of Acid Mine Drainage: Effect of Rock Type and Amendment. Proceedings Twelfth Annual West Virginia Surface Mine Drainage Task Force Symposium, April 3-4, Morgantown, West Virginia, Vol.1, 51-54.